Left atrium phasic function decreases in adult patients with repaired tetralogy of fallot: a case–control study - Keiya Sato; Ken Takahashi; Yusuke Akatsuka; Hiroyuki Sato; Hirohisa Kago; Azusa Akiya; Satoshi Akimoto; Mayumi Ifuku; Yu Hosono; Sachie Shigemitsu; Kotoko Matsui; Keisuke Nakanishi; et al. (Cardiovascular Ultrasound)
Abstract Background Although the left atrium (LA) plays a key role in diastolic function, LA dysfunction in patients with repaired tetralogy of Fallot (rTOF) remains unclear. Recently, LA strains assessed using a speckle tracking system have been used as novel sensitive indicators of LA function. Therefore, we aimed to evaluate LA function and investigate changes with age in patients with rTOF using speckle-tracking echocardiography. Methods We analyzed three age-based subgroups of patients with rTOF (T1, T2, T3) and their corresponding healthy control groups (C1, C2, C3) to assess phasic left atrial function: T1 and C1 (3–9 years [children]), T2 and C2 (10–19 years [adolescents and young adults]), and T3 and C3 (20–44 years [adults]). LA strain was assessed by two-dimensional speckle-tracking echocardiography and defined according to its three distinct phases, with the LA serving as a reservoir during systole, a conduit during early diastole, and a booster pump at the end of diastole. Furthermore, we examined the correlations between LA strains and left ventricular longitudinal strain (LVLS) as well as conventional echocardiographic parameters. Results LA reservoir and pump strains were lower in the T3 group than in the C3 group (35.5 (30.1/41.3) vs. 42.9 (41.1/48.1), P = 0.010; 8.3 (7.4/10.6) vs. 11.4 (10.7/13.5), P = 0.025, respectively). In the T1 and T2 groups, no significant differences in LA strains were reported. LA functions based on LA volume did not show any difference between rTOF and controls among all age groups. All LA strains only moderately or weakly correlated with LVLS and mitral E/A, but not with left ventricular (LV) lateral e’ nor E/e’. Reservoir strain-LVLS (ρ = 0.476, P < 0.001), conduit strain-LVLS (r = 0.382, P < 0.001), pump strain-LVLS (ρ = 0.337, P < 0.001), reservoir strain-E/A (ρ = 0.200, P = 0.026), conduit strain-E/A (ρ = 0.282, P = 0.002), and pump strain-E/A (ρ = −0.209, P = 0.02). Conclusions LA phasic function decreases in adult patients with rTOF. LA reservoir and pump strains may serve as sensitive indicators of diastolic dysfunction in these patients.